2019
DOI: 10.3390/molecules24224064
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Discrimination of Astragalus mongholicus and Astragalus membranaceus Based on Metabolomics Using UHPLC-ESI-Q-TOF-MS/MS Approach

Abstract: Astragalus mongholicus (MG) and Astragalus membranaceus (MJ), both generally known as Huangqi in China, are two perennial herbals widely used in variety diseases. However, there were still some differences in the chemical ingredients between MG and MJ. In this paper, metabolomics combined with the ultra-high performance liquid chromatography coupled with electrospray ionization/quadrupole time-of-flight mass spectrometry (UHPLC-ESI-Q-TOF-MS/MS) was employed to contrastively analyze the chemical constituents be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Ononin has multiple physiological functions, such as antioxidant, antimicrobial and anti-inflammatory activities (Yu et al, 2016). Additionally, people also found Ononin could promote skin growth, scaveng oxygen free radicals, inhibit lipid peroxidation, maintain the concentration of nitric oxide in blood, protect ischemia-reperfusion injury and enhance immunity (Wang et al, 2019). In view of its so many important physiological functions, we speculated that it had a special effect in fighting against RA.…”
Section: Discussionmentioning
confidence: 97%
“…Ononin has multiple physiological functions, such as antioxidant, antimicrobial and anti-inflammatory activities (Yu et al, 2016). Additionally, people also found Ononin could promote skin growth, scaveng oxygen free radicals, inhibit lipid peroxidation, maintain the concentration of nitric oxide in blood, protect ischemia-reperfusion injury and enhance immunity (Wang et al, 2019). In view of its so many important physiological functions, we speculated that it had a special effect in fighting against RA.…”
Section: Discussionmentioning
confidence: 97%
“…It was discovered that CTX and HC mainly affected amino acid metabolism and energy metabolism, which is consistent with previous reports. 15 , 24 , 25 Besides, the enrichment analysis revealed that A4 was more inclined to regulate body’s amino acid metabolism in CTX-rats and energy metabolism in HC-rats.
Figure 10 A schematic diagram showing amino acids metabolism and energy metabolism interacting with each other during A4 treatment.
…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recognized that AMM is a varied species of AM 83–85 . Recent LC‐MS analysis indicated that the two herbs had significant differences in the contents of some chemical markers 77,86 . Here, we further discuss their structural differences by comparing the 189 compounds that have been isolated from AM and AMM.…”
Section: Chemical Constituents Of Am and Ammmentioning
confidence: 92%
“…Cycloartane‐type triterpenoids are rare in nature. They have only been reported from a few plants, such as those from Astragalus, Cimicifuga , and Schisandra species 78–90 . Thus far, a total of 51 cycloartane‐type triterpenoids and saponins ( 1 – 51 ) have been isolated and identified from AM and AMM; and these two species share 12 common compounds ( 1, 5 – 11, 13, 21 – 22, 31 ).…”
Section: Chemical Constituents Of Am and Ammmentioning
confidence: 99%